Exploring the barriers to online student learning support services: A review - Enwereji, P.; Van Rooyen, A. (South African Journal of Higher Education, 2025)
Online education has been proven by several scholars as a convenient, flexible, and successful means of teaching and learning. Given the rate of student dropout in online learning, and the outbreak of the Covid-19 pandemic, this study explored the barriers to online students’ learning support services. A qualitative research approach was applied, and a non-empirical methodological approach was adopted. In this case, literature sources were reviewed to identify the barriers to online learning support services. One hundred articles related to e-learning were downloaded from Google Scholar, 80 of the articles were deemed irrelevant and discarded, and 20 articles were analyzed and used for this study. During the analysis, multiple barriers to online learning were identified and documented, and related barriers were later grouped into themes. Findings depict that the barriers to online learning as being personal constraints, enabling conditions, social interactions, pedagogy, technology, and motivational issues. The study, therefore, recommends that institutions providing online teaching in South Africa, and in other parts of the world, should ensure that there is adequate communication between students and academics. The study further provides appropriate recommendations to alleviate online learning barriers identified by the study. These institutions must guide and offer comprehensive motivation to ensure each student will learn with utmost enthusiasm.